Low-alkalinity and early-strength ardealite filling curing material and preparation method thereof

By using specific formulas of low alkalinity and early strength phosphogypsum filling curing materials in phosphogypsum filling technology, the problems of retarding, low early strength, high alkalinity and high water secretion in phosphogypsum filling are solved, and rapid initial solidification and early strength are improved, while reducing the water secretion rate of the slurry and the alkalinity of the filler.

CN119751012AActive Publication Date: 2025-04-04SICHUAN INSITITUTE OF BUILDING RES +2

Patent Information

Application Number
CN202510268371.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-07
Publication Date
2025-04-04
Estimated Expiration
2045-03-07

AI Technical Summary

Technical Problem

Among the existing phosphogypsum filling technology, conventional silicate cement, as a cured material, has problems such as low early strength, high overall alkalinity and high water secretion, and it is difficult to meet the requirements of phosphogypsum cementing and filling technology.

Method used

The low-alkali and early-strength phosphogypsum filling curing materials are used. The raw material formula includes phosphogypsum, curing agent and water. The curing agent is composed of silica fume, limestone powder, ultra-fine granulated blast furnace slag powder, metakaolin, aluminate cement, silicate cement clinker powder, suspension stabilizer and hydroxypropyl methylcellulose ether. By adjusting the formula and component ratio, the initial settling time, early strength and alkalinity of the filling are controlled.

Benefits of technology

The rapid initial condensation of phosphogypsum filler slurry under large amounts of phosphogypsum was achieved, and the early strength was improved (3d compressive strength ≥1MPa, 7d compressive strength ≥3MPa, 28d strength ≥5MPa), which reduced the water secretion rate of the slurry and the alkalinity of the filler, and met the technical requirements of phosphogypsum cementing and filling technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751012A_ABST
    Figure CN119751012A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of new building materials, and provides a low-alkalinity and early-strength ardealite filling and curing material and a preparation method thereof.The low-alkalinity and early-strength ardealite filling and curing material is prepared from ardealite, a curing agent and water, the curing agent comprises silica fume, limestone powder, superfine granulated blast furnace slag powder, metakaolin, calcium aluminate powder, Portland cement clinker powder, a suspension stabilizer and hydroxypropyl methyl cellulose ether. The problems of delayed coagulation, low early strength and high alkalinity of a common cement-based ardealite filling material can be solved, and the technical requirements of ardealite cemented filling are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new building materials, and more specifically, relates to a low-alkalinity, early-strength phosphogypsum filling and curing material and a preparation method thereof. Background Art

[0002] Phosphogypsum cementing filling technology is an effective way to harmlessly utilize phosphogypsum proposed in recent years. Phosphogypsum filling technology uses phosphogypsum as the main raw material, solidifying materials (such as silicate cement, fly ash, etc.) and other additives (such as activators, water reducers, etc.) to solidify the materials. After the above materials are mixed with water to form a homogeneous mixed slurry, they are backfilled into the goaf of underground mines. As the hydration reaction proceeds, the filling body gradually forms strength. After consolidation and hardening, it supports the roof of the underground goaf, prevents surface subsidence, and increases the recovery rate of phosphate ore. It not only achieves safe and efficient recovery of resources, but also effectively alleviates environmental problems caused by surface solid waste storage.

[0003] However, conventional solidifying materials such as silicate cement are difficult to meet the technical requirements of phosphogypsum cementing and filling: ① The phosphogypsum filling body with conventional silicate cement as the curing material has a serious slow setting phenomenon. In the case of a large amount of phosphogypsum, the initial setting time of the filling slurry is usually more than 48 hours.

[0004] ② The overall alkalinity of the phosphogypsum filling body using conventional silicate cement as the solidifying material is high, and the pH of its leaching solution can usually reach about 12.5. The dissolution of hydroxide ions in the filling body will affect the pH value of the surrounding groundwater.

[0005] ③ The phosphogypsum with conventional silicate cement as the curing material has a high water seepage rate. The soluble fluorine, phosphorus, heavy metals and other pollutants in the gypsum filling body affect the water and soil environment through exudation.

[0006] In order to solve the above problems of phosphogypsum cementing filling, it is urgent to develop a new type of phosphogypsum filling and curing material. Summary of the invention

[0007] One of the purposes of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a low-alkalinity, early-strength phosphogypsum filling and curing material.

[0008] One aspect of the present invention provides a low-alkalinity, early-strength phosphogypsum filling and curing material, wherein the raw material formula of the low-alkalinity, early-strength phosphogypsum filling and curing material includes phosphogypsum, a curing agent and water, wherein the phosphogypsum is dihydrate phosphogypsum, the phosphogypsum accounts for 65-75 parts on a dry basis, the curing agent accounts for 25-35 parts, and the water accounts for 27%-34% of the sum of the phosphogypsum and the curing agent by weight, wherein the curing agent includes silica fume, limestone powder, ultrafine granulated blast furnace slag powder, metakaolin, aluminate cement, silicate cement clinker powder, suspension stabilizer, and hydroxypropyl methylcellulose ether, and by mass percentage, the content of aluminate cement is 6-8%, the content of silicate cement clinker powder is 28-32%, the aluminate cement includes calcium aluminate powder, the calcium aluminate powder includes monocalcium aluminate and / or monocalcium dialuminate, and the calcium carbonate content of the limestone powder is ≥80%.

[0009] In an embodiment, the specific surface area of ​​the calcium aluminate powder is ≥400m 2 / kg, Al2O3≥50%. In an embodiment, the curing agent may be composed of the following components by mass percentage: silica fume 4-6%, limestone powder 9-11%, ultrafine granulated blast furnace slag powder 36-41%, metakaolin 8-12%, calcium aluminate powder 6-8%, silicate cement clinker powder 28-32%, suspension stabilizer 0.3-3‰, hydroxypropyl methylcellulose ether 0.5-1.5‰.

[0010] In the embodiment, the silica fume can be semi-densified or fully-densified silica fume, with a silicon dioxide content of ≥95%, an activity index of ≥110%, and a water requirement ratio of ≤125%; the fineness of the limestone powder is 1000 mesh or above; the specific surface area of ​​the ultrafine granulated blast furnace slag powder is ≥600m 2 / kg, 28d activity index ≥105%; Al2O3 in the kaolin powder ≥35%, specific surface area ≥600m 2 / kg, 28d activity index ≥105%; the tricalcium silicate content of the silicate cement clinker powder is ≥55%, and the specific surface area is ≥350m 2 / kg; the particle size of the phosphogypsum is ≤4.75mm.

[0011] In an embodiment, the phosphogypsum may account for ≥65% of the dry material mass, the dry material may include phosphogypsum and a curing agent, the initial setting time of the phosphogypsum filling and curing material is ≤8h, the 3d compressive strength is ≥1MPa, the 7d compressive strength is ≥3MPa, the 28d strength is ≥5MPa, the filling slurry expansion is ≥800mm, the slurry water seepage rate is ≤0.5%, and the 28d filling body leachate pH value is ≤10.

[0012] According to another aspect of the present invention, a method for preparing a low-alkalinity, early-strength phosphogypsum filling and curing material is provided, the preparation method comprising: mixing silica fume, limestone powder, ultrafine granulated blast furnace slag powder, metakaolin, aluminate cement, silicate cement clinker powder, suspension stabilizer, and hydroxypropyl methylcellulose ether to form a curing agent powder, wherein the aluminate cement comprises calcium aluminate powder, the calcium aluminate powder comprises monocalcium aluminate and / or monocalcium dialumate, and the calcium carbonate content of the limestone powder is ≥80%. , by mass percentage, the content of aluminate cement is 6-8%, and the content of silicate cement clinker powder is 28-32%; water and the curing agent powder are mixed evenly to obtain curing agent slurry; and phosphogypsum is added to the curing agent slurry until the slurry is mixed evenly to obtain phosphogypsum filling slurry; wherein the phosphogypsum is dihydrate phosphogypsum, the phosphogypsum is 65-75 parts on a dry basis, the curing agent is 25-35 parts, and water accounts for 27%-34% by weight of the sum of the phosphogypsum and the curing agent.

[0013] In an embodiment, the specific surface area of ​​the calcium aluminate powder is ≥400m 2 / kg, Al2O3≥50%.

[0014] In the embodiment, in the step of forming the curing agent powder, by mass percentage, silica fume 4-6%, limestone powder 9-11%, ultrafine granulated blast furnace slag powder 36-41%, metakaolin 8-12%, calcium aluminate powder 6-8%, silicate cement clinker powder 28-32%, suspension stabilizer 0.3-3‰, and hydroxypropyl methylcellulose ether 0.5-1.5‰.

[0015] In the embodiment, the silica fume can be semi-densified or fully-densified silica fume, with a silicon dioxide content of ≥95%, an activity index of ≥110%, and a water requirement ratio of ≤125%; the fineness of the limestone powder is 1000 mesh or above; the specific surface area of ​​the ultrafine granulated blast furnace slag powder is ≥600m 2 / kg, 28d activity index ≥105%; the metakaolin powder can be a powder material with amorphous aluminum silicate as the main component obtained by calcining kaolin minerals at 600-900°C, wherein Al2O3 in the metakaolin powder is ≥35%, and the specific surface area is ≥600m 2 / kg, 28d activity index ≥105%; the tricalcium silicate content of the silicate cement clinker powder is ≥55%, and the specific surface area is ≥350m 2 / kg; the particle size of the phosphogypsum is ≤4.75mm.

[0016] In an embodiment, the phosphogypsum may account for ≥65% of the dry material mass, and the dry material may include phosphogypsum and a curing agent. The initial setting time of the phosphogypsum filling curing material is ≤8h, the 3d compressive strength is ≥1MPa, the 7d compressive strength is ≥3MPa, the 28d strength is ≥5MPa, the filling slurry expansion is ≥800mm, the slurry water seepage rate is ≤0.5%, and the 28d filling body leachate pH value is ≤10.

[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention can solve the problems of slow setting, low early strength and high alkalinity of ordinary cement-based phosphogypsum filling, and can achieve the following conditions: when the filling slurry has a large amount of phosphogypsum (phosphogypsum accounts for ≥65% of the dry material mass), the initial setting time of the filling slurry is ≤8h, the 3d compressive strength is ≥1MPa, the 7d compressive strength is ≥3MPa, the 28d strength is ≥5MPa, the expansion of the filling slurry is ≥800mm, the slurry water bleeding rate is ≤0.5%, and the pH of the 28d filling body leachate is ≤10, which meets the technical requirements for phosphogypsum cementing filling. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The accompanying drawings illustrate exemplary embodiments of the inventive concept and, together with the description, serve to explain the principles of the inventive concept. The accompanying drawings are included to provide a further understanding of the inventive concept and are incorporated in and constitute a part of this specification.

[0019] Figure 1 The material test results of the phosphogypsum filling and curing materials according to the examples of the present invention and the comparative examples are shown. DETAILED DESCRIPTION

[0020] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0021] Reasons for using phosphogypsum filling and curing agent: The main component of phosphogypsum is calcium sulfate dihydrate (CaSO4·2H2O), which is not water-hardening. The filling slurry formed after mixing with water has no strength. Curing materials need to be added to cement the phosphogypsum to give the filling slurry strength.

[0022] Problems with using pure silicate cement as a filling and curing agent: Micro-silicate cement, a conventional curing agent, is a representative hydraulic material. However, when using silicate cement as a single cementing material to cure a large amount of phosphogypsum, the initial setting time of the filling slurry is usually more than 48 hours. This is because the gypsum component and soluble phosphorus in the phosphogypsum react with silicate cement, hindering the hydration reaction of silicate cement, resulting in a significant delay in its retarding time and a significant reduction in its early strength. At the same time, the hydration product of the system contains a large amount of Ca(OH)2, resulting in a high pH, ​​which makes it difficult to meet the application requirements of performance such as setting time, early strength, and pH value.

[0023] Problems with "Portland cement + granulated blast furnace slag powder" or "Portland cement + lime + granulated blast furnace slag powder" as filling and curing agents: Granulated blast furnace slag powder reacts with phosphogypsum and cement or lime hydration product Ca(OH)2 to generate hydration products such as calcium aluminate and C-(A)-SH gel. This system can achieve a certain degree of improvement in the mechanical properties of the hardened cementitious body, but this system still does not solve the problems of long setting time, high alkalinity and low early strength caused by the inhibitory effect of phosphogypsum on the hydration reaction of composite cementitious materials.

[0024] To solve the above problems, the technical concept of the present invention is: One aspect of the present invention provides a low-alkalinity, early-strength phosphogypsum filling and curing material. In an exemplary embodiment, the raw material formula of the low-alkalinity, early-strength phosphogypsum filling and curing material includes phosphogypsum, a curing agent and water, wherein the curing agent includes silica fume, limestone powder, ultrafine granulated blast furnace slag powder, metakaolin, calcium aluminate powder, silicate cement clinker powder, a suspension stabilizer, and hydroxypropyl methylcellulose ether.

[0025] The exemplary embodiment of the present invention can solve the technical problems of slow setting, low early strength and high alkalinity of phosphogypsum, so as to meet the technical requirements of phosphogypsum cementitious filling.

[0026] The exemplary embodiment of the present invention solves the mechanism of slow setting and low early strength of conventional phosphogypsum: (1) The present invention is based on the characteristics of sufficient phosphogypsum and water in the phosphogypsum filling slurry. The "Portland cement, aluminate cement, granulated blast furnace slag powder, and metakaolin" components in the curing agent react with the gypsum phase under sufficient water conditions to achieve a cementing and curing effect.

[0027] The C3A component in silicate cement forms hydrated calcium aluminate (C3AH6) which reacts with gypsum and water to form a highly hydrated reaction product - calcium sulfonate (C6AS3H 32), the generated calcium sulfonite usually covers the surface of cement particles to hinder the further reaction of silicate cement particles. At the same time, the soluble phosphorus in phosphogypsum will also react with silicate cement to form insoluble substances, hindering the reaction, thereby causing serious slow setting of the phosphogypsum filling. The present invention introduces aluminate cement, which is a cement with calcium aluminate as the main mineral composition. Its main components are monocalcium aluminate (CA) and monocalcium dialuminate (C2A). It will also react with gypsum in this system to produce calcium sulfonite to cover the surface, but there is sufficient aluminum phase in the aluminate cement particles. Some aluminate ions are dissolved into the water through penetration, dissolution, etc., and continue to react with the gypsum phase to form hydration products that are interwoven and constructed between various particles, greatly shortening the initial setting time of the system and ensuring its early strength. At the same time, the granulated blast furnace slag powder and metakaolin in the curing agent, under the action of calcium hydroxide, the cement hydration product, dissolve aluminosilicate ions, silicate ions, etc., and react with the gypsum phase to produce hydration products C-(A)-SH gel and calcium aluminate, which makes the phosphogypsum filling body continuously dense and increases the later strength.

[0028] (2) The "aluminate cement, kaolin, and limestone" in the curing agent can react with the "gypsum and silicate cement hydration products" in the system to achieve a bonding and curing effect.

[0029] In the exemplary embodiment of the present invention, calcium aluminate reacts with ultrafine limestone powder (mainly calcium carbonate) and calcium hydroxide to generate hydrated calcium aluminate. This reaction mainly occurs in the early stage of hydration, and the hydration rate is relatively fast, which can adjust the early setting time and early strength of the phosphogypsum filling slurry. Amorphous aluminosilicate (AlSi2O3) in metakaolin is dissolved under alkaline conditions and can react with calcium hydroxide, gypsum, and limestone powder (calcium carbonate) to generate C-(A)-SH, hydrated calcium aluminate, and ettringite to form strength. The hydrated calcium aluminate formed above is relatively dense and provides strength for the filling body. This reaction mainly occurs in the middle and late stages of the system reaction.

[0030] In an embodiment, phosphogypsum is original phosphogypsum that has not been subjected to high-temperature treatment such as calcination. The phosphogypsum may be wet phosphogypsum dried at 40°C to dihydrate phosphogypsum of constant weight, and the phosphogypsum accounts for ≥65% of the dry material mass, where the dry material refers to phosphogypsum and a curing agent.

[0031] In an embodiment, the production raw material formula may include the following components in the following mass proportions: 65-75 parts of phosphogypsum (on a dry basis), 25-35 parts of a curing agent, and water accounting for 27%-34% by weight of the sum of the phosphogypsum and the curing agent.

[0032] Among them, the curing agent can be composed of the following components in percentage by mass: 4-6% silica fume, 9-11% limestone powder, 36-41% ultrafine granulated blast furnace slag powder, 8-12% metakaolin, 6-8% calcium aluminate powder, 28-32% silicate cement clinker powder, 0.3-3‰ suspension stabilizer, and 0.5-1.5‰ hydroxypropyl methylcellulose ether.

[0033] Exemplarily, the silica fume may be semi-densified or fully-densified silica fume with a silicon dioxide content ≥ 95%, an activity index ≥ 110%, and a water demand ratio ≤ 125%.

[0034] Exemplarily, the calcium carbonate content of the limestone powder is ≥80%, and the fineness is 1000 mesh and above.

[0035] For example, the specific surface area of ​​the ultrafine granulated blast furnace slag powder is ≥ 600m 2 / kg, 28d activity index ≥105%. Within this specific surface area range, granulated blast furnace slag is more reactive and activated.

[0036] For example, the metakaolin powder can be a powder material obtained by calcining kaolin minerals at 600-900°C and containing amorphous aluminum silicate as a main component, wherein the Al2O3 content in the metakaolin powder is ≥35% and the specific surface area is ≥600m 2 / kg, 28d activity index ≥105%.

[0037] For example, the calcium aluminate powder may include monocalcium aluminate and / or monocalcium dialuminate, with a specific surface area of ​​≥400 m 2 / kg, Al2O3≥50%.

[0038] For example, the tricalcium silicate content of the silicate cement clinker powder is ≥55%, and the specific surface area is ≥350m 2 Illustratively, the Portland cement clinker powder may include 50-70% tricalcium silicate, 20-40% dicalcium silicate, 6-12% tricalcium aluminate and 10-20% tetracalcium aluminoferrate.

[0039] For example, the suspension stabilizer (also called suspension dispersant) can be a light yellow powder, and the addition can improve the suspension performance and stability of particles in the filling slurry. For example, the suspension stabilizer can include modified vinyl alcohol polymers, vinyl ester polymers, maltodextrin, etc.

[0040] For example, hydroxypropyl methylcellulose (HPMC) can be a white powder with a viscosity of 200,000 and an industrial purity.

[0041] For example, the particle size of phosphogypsum is ≤4.75mm, and other indicators should meet the technical requirements of the current national standard GB / T23456 "Phosphogypsum".

[0042] For example, the water may be water that meets the requirements of the current industry standard "Standard for Water Use in Concrete" JGJ 63.

[0043] The exemplary embodiment of the present invention solves the mechanism of high alkalinity of conventional cement-based phosphogypsum filling cement-based phosphogypsum filling system: The reactant that produces alkalinity in the reaction system of the exemplary embodiment of the present invention is mainly silicate cement, which itself accounts for only 28-32% of the curing agent and 7-12% of the phosphogypsum filling body, and its relative content is low. Its reactant calcium hydroxide is the main source of alkalinity, and the silica fume, metakaolin, and granulated blast furnace slag in the curing agent all react with calcium hydroxide to reduce the alkalinity of the system. At the same time, the curing agent of the exemplary embodiment of the present invention provides strength aluminate cement and limestone powder, and its main hydration products are hydrated calcium aluminate and calcium sulfonate, and no calcium hydroxide is generated, so the alkalinity of the entire system is low.

[0044] The mechanism of good working performance of the low-alkalinity, early-strength phosphogypsum filling and curing material of the exemplary embodiment of the present invention is as follows: the content of silicate and aluminate cement in the reaction system is scientific, the setting time is controllable under the phosphogypsum filling system, and no flash setting occurs. The silica fume in the system plays a role of lubrication of glass beads, the suspending dispersant in the system can make the phosphogypsum better suspended in water, stabilize the slurry, and make the slurry have a better fluidity, and the hydroxymethyl ethyl cellulose can play a role of water retention and reduce water exudation in the system.

[0045] In an embodiment, phosphogypsum may account for ≥65% of the dry material mass, the dry material may include phosphogypsum and a curing agent, the initial setting time of the phosphogypsum filling and curing material is ≤8h, the 3d compressive strength is ≥1MPa, the 7d compressive strength is ≥3MPa, the 28d strength is ≥5MPa, the filling slurry expansion is ≥800mm, the slurry water seepage rate is ≤0.5%, and the 28d filling body leachate pH value is ≤10.

[0046] According to another aspect of the present invention, there is provided a method for preparing a low-alkalinity, early-strength phosphogypsum filling and curing material, the preparation method comprising: mixing silica fume, limestone powder, ultrafine granulated blast furnace slag powder, metakaolin, calcium aluminate powder, silicate cement clinker powder, a suspension stabilizer, and hydroxypropyl methylcellulose ether to form a curing agent powder; mixing water and the curing agent powder to obtain a curing agent slurry; adding phosphogypsum to the curing agent slurry and mixing the slurry to obtain a phosphogypsum filling slurry.

[0047] In an exemplary embodiment, phosphogypsum accounts for ≥ 65% of the mass of the dry material, and the dry material includes phosphogypsum and a curing agent.

[0048] The components are calculated by weight: 65-75 parts of phosphogypsum (on a dry basis), 25-35 parts of a curing agent, and water accounts for 27%-34% of the sum of the phosphogypsum and the curing agent by weight.

[0049] In the step of forming the curing agent powder, by mass percentage, silica fume 4-6%, limestone powder 9-11%, ultrafine granulated blast furnace slag powder 36-41%, metakaolin 8-12%, calcium aluminate powder 6-8%, silicate cement clinker powder 28-32%, suspension stabilizer 0.3-3‰, and hydroxypropyl methylcellulose ether 0.5-1.5‰.

[0050] Exemplarily, the limestone powder may be semi-densified or fully-densified silica fume, with a silicon dioxide content ≥ 95%, an activity index ≥ 110%, and a water demand ratio ≤ 125%.

[0051] Exemplarily, the calcium carbonate content of the limestone powder is ≥80%, and the fineness is 1000 mesh and above.

[0052] For example, the specific surface area of ​​the ultrafine granulated blast furnace slag powder is ≥ 600m 2 / kg, 28d activity index ≥105%.

[0053] For example, the metakaolin powder can be a powder material obtained by calcining kaolin minerals at 600-900°C and containing amorphous aluminum silicate as a main component, wherein the Al2O3 content in the metakaolin powder is ≥35% and the specific surface area is ≥600m 2 / kg, 28d activity index ≥105%.

[0054] For example, the calcium aluminate powder may include monocalcium aluminate and / or monocalcium dialuminate, with a specific surface area of ​​≥400 m 2 / kg, Al2O3≥50%.

[0055] For example, the tricalcium silicate content of the silicate cement clinker powder is ≥55%, and the specific surface area is ≥350m 2 / kg.

[0056] For example, the suspension stabilizer can be a light yellow powder, and the addition can improve the suspension performance and stability of the particles in the filling slurry. For example, the suspension stabilizer can include modified vinyl alcohol polymers, vinyl ester polymers, maltodextrin, and the like.

[0057] For example, hydroxypropyl methylcellulose (HPMC) can be a white powder with a viscosity of 200,000 and an industrial purity.

[0058] For example, the particle size of phosphogypsum is ≤4.75mm, and other indicators should meet the technical requirements of the current national standard GB / T23456 "Phosphogypsum".

[0059] For example, the water may be water that meets the requirements of the current industry standard "Standard for Water Use in Concrete" JGJ 63.

[0060] In an embodiment, phosphogypsum may account for ≥65% of the dry material mass, the dry material may include phosphogypsum and a curing agent, the initial setting time of the phosphogypsum filling and curing material is ≤8h, the 3d compressive strength is ≥1MPa, the 7d compressive strength is ≥3MPa, the 28d strength is ≥5MPa, the filling slurry expansion is ≥800mm, the slurry water seepage rate is ≤0.5%, and the 28d filling body leachate pH value is ≤10.

[0061] In another exemplary embodiment, the method for preparing the low-alkalinity, early-strength phosphogypsum filling and curing material of the above exemplary embodiment comprises the following steps: S1. Wet phosphogypsum should be dried at 40℃ to constant weight and its moisture content should be calculated.

[0062] S2. Weigh each raw material according to the production raw material formula. The weighed phosphogypsum raw material is the mass of dry phosphogypsum converted by moisture content, and the weighed water should be deducted from the moisture contained in the wet phosphogypsum.

[0063] S3. Evenly mix the silica fume, limestone powder, ultrafine granulated blast furnace slag powder, metakaolin, calcium aluminate powder, silicate cement clinker powder, suspension stabilizer and hydroxypropyl methylcellulose ether required for the curing agent components in a dry mixing device to form a filling curing agent powder.

[0064] S4. Mix water and curing agent powder evenly in a stirring device to obtain curing agent slurry.

[0065] S5. Add the phosphogypsum into the curing agent slurry at a uniform speed until the slurry is evenly mixed to obtain the phosphogypsum filling slurry.

[0066] S6. Inject the phosphogypsum filling slurry into the position to be filled, and after molding and curing to an age of 3 days or more, a filling body with strength is obtained.

[0067] In an exemplary embodiment, a method for preparing a low-alkalinity, early-strength phosphogypsum filling and curing material is provided, and the obtained phosphogypsum filling slurry can be backfilled into the goaf of underground mines. As the hydration reaction proceeds, the filling body gradually develops strength, and after consolidation and hardening, it supports the roof of the underground goaf, prevents surface subsidence, and increases the recovery rate of phosphate ore, which not only achieves safe and efficient recovery of resources, but also effectively alleviates environmental problems caused by the storage of surface solid waste.

[0068] In an exemplary embodiment, a low-alkalinity, early-strength phosphogypsum filling and curing material can be prepared by the above-mentioned preparation method.

[0069] In an exemplary embodiment, the low-alkalinity, early-strength phosphogypsum filling and curing material prepared by the preparation method described above or the low-alkalinity, early-strength phosphogypsum filling and curing material described above is used in the curing material used in the phosphogypsum cementing filling technology.

[0070] In an embodiment, the backfill can be used to fill the goaf of an underground mine; as the hydration reaction proceeds, the filling body gradually develops strength, and after consolidation and hardening, it supports the roof of the goaf.

[0071] In order to better understand the above exemplary embodiments of the present invention, they are further described below in conjunction with specific examples. It should be noted that the raw material sources and specific component compositions used in the following examples are consistent, for example, the silicate cement clinker powder in Example 1 is the same as the silicate cement clinker powder in Example 2.

[0072] Example 1 Prepare low-alkalinity, early-strength phosphogypsum filling and curing material according to the following steps: S1. Wet phosphogypsum should be dried at 40℃ to constant weight and its moisture content should be calculated.

[0073] S2, 70 parts of dihydrate phosphogypsum (on a dry basis), 30 parts of curing agent component; water accounts for 32% of the sum of phosphogypsum and curing agent by weight. Among them, the curing agent is composed of 5% silica fume, 10% limestone powder, 38% ultrafine granulated blast furnace slag powder, 10% metakaolin, 7% calcium aluminate powder, 30% silicate cement clinker powder, 1‰ suspension stabilizer, and 1‰ hydroxypropyl methylcellulose ether by mass ratio. Weigh each raw material, where the weighed phosphogypsum raw material is the mass of dry phosphogypsum converted by moisture content, and the weighed water should be discounted by the moisture contained in the wet phosphogypsum.

[0074] S3. Evenly mix the silica fume, limestone powder, ultrafine granulated blast furnace slag powder, metakaolin, calcium aluminate powder, silicate cement clinker powder, suspension stabilizer and hydroxypropyl methylcellulose ether required for the curing agent components in a dry mixing device to form a filling curing agent powder.

[0075] S4. Mix water and curing agent powder evenly in a stirring device to obtain curing agent slurry.

[0076] S5. Add the phosphogypsum into the curing agent slurry at a uniform speed until the slurry is evenly mixed to obtain the phosphogypsum filling slurry.

[0077] S6. Take part of the filling material slurry to test its expansion, take another part of the filling material slurry to test its water seepage rate, and put the remaining phosphogypsum filling material slurry into the setting time mold and the 70.7×70.7×70.7mm triple mold for setting time test and compressive strength test respectively. After curing to the specified age, test the compressive strength and pH value of the leachate.

[0078] The testing methods for the above items are carried out in the following manner: The test methods for the expansion and water seepage rate of the filling slurry are carried out in accordance with the current national standard "Standard for Performance Test Methods of Ordinary Concrete Mixtures" GB / T 50080. The test method for the setting time of the filling slurry is carried out in accordance with the current national standard "Test Methods for Water Consumption, Setting Time and Stability of Cement Standard Consistency" GB / T 1346. The compressive strength test is carried out in accordance with the current industry standard "Test Methods for Basic Properties of Building Mortar" JGJ70. For the pH test, the test blocks cured to 28 days old are crushed to a maximum particle size of no more than 4.75mm, mixed with deionized water at a solid-liquid ratio of 1:10, and after standing for 24 days, the supernatant is taken and the pH value is tested with a pH meter.

[0079] Example 2 Prepare low-alkalinity, early-strength phosphogypsum filling and curing material according to the following steps: S1. Wet phosphogypsum should be dried at 40℃ to constant weight and its moisture content should be calculated.

[0080] S2, 65 parts of dihydrate phosphogypsum (on a dry basis), 35 parts of curing agent component; water accounts for 31% of the sum of phosphogypsum and curing agent by weight. The curing agent contains 5% silica fume, 10% limestone powder, 36% ultrafine granulated blast furnace slag powder, 9% metakaolin, 8% calcium aluminate powder, 32% silicate cement clinker powder, 0.5‰ suspension stabilizer, and 0.8‰ hydroxypropyl methylcellulose ether. Weigh each raw material, where the weighed phosphogypsum raw material is the mass of dry phosphogypsum converted by moisture content, and the weighed water should be discounted by the moisture contained in the wet phosphogypsum.

[0081] S3. Evenly mix the silica fume, limestone powder, ultrafine granulated blast furnace slag powder, metakaolin, calcium aluminate powder, silicate cement clinker powder, suspension stabilizer and hydroxypropyl methylcellulose ether required for the curing agent components in a dry mixing device to form a filling curing agent powder.

[0082] S4. Mix water and curing agent powder evenly in a stirring device to obtain curing agent slurry.

[0083] S5. Add the phosphogypsum into the curing agent slurry at a uniform speed until the slurry is evenly mixed to obtain the phosphogypsum filling slurry.

[0084] S6. Take part of the filling material slurry to test its expansion, take another part of the filling material slurry to test its water seepage rate, and put the remaining phosphogypsum filling material slurry into the setting time mold and the 70.7×70.7×70.7mm triple mold for setting time test and compressive strength test respectively. After curing to the specified age, test the compressive strength and pH value of the leachate.

[0085] The material detection method is the same as in Example 1 and will not be described again here.

[0086] Example 3 Prepare low-alkalinity, early-strength phosphogypsum filling and curing material according to the following steps: S1. Wet phosphogypsum should be dried at 40℃ to constant weight and its moisture content should be calculated.

[0087] S2, 75 parts of dihydrate phosphogypsum (on a dry basis), 25 parts of curing agent component; water accounts for 32% of the sum of phosphogypsum and curing agent by weight. The curing agent contains 4% silica fume, 9% limestone powder, 41% ultrafine granulated blast furnace slag powder, 8% metakaolin, 6% calcium aluminate powder, 32% silicate cement clinker powder, 0.5‰ suspension stabilizer, and 0.8‰ hydroxypropyl methylcellulose ether. Weigh each raw material, where the weighed phosphogypsum raw material is the mass of dry phosphogypsum converted by moisture content, and the weighed water should be discounted by the moisture contained in the wet phosphogypsum.

[0088] S3. Evenly mix the silica fume, limestone powder, ultrafine granulated blast furnace slag powder, metakaolin, calcium aluminate powder, silicate cement clinker powder, suspension stabilizer and hydroxypropyl methylcellulose ether required for the curing agent components in a dry mixing device to form a filling curing agent powder.

[0089] S4. Mix water and curing agent powder evenly in a stirring device to obtain curing agent slurry.

[0090] S5. Add the phosphogypsum into the curing agent slurry at a uniform speed until the slurry is evenly mixed to obtain the phosphogypsum filling slurry.

[0091] S6. Take part of the filling slurry for slurry test on its expansion, take another part of the filling slurry for slurry test on its water seepage rate, and put the remaining phosphogypsum filling slurry into the setting time mold and the 70.7×70.7×70.7mm triple mold for setting time test and compressive strength test respectively. After curing to the specified age, test the compressive strength and pH value of the leachate.

[0092] The material detection method is the same as in Example 1 and will not be described again here.

[0093] Example 4 Prepare low-alkalinity, early-strength phosphogypsum filling and curing material according to the following steps: S1. Wet phosphogypsum should be dried at 40℃ to constant weight and its moisture content should be calculated.

[0094] S2, 65 parts of dihydrate phosphogypsum (on a dry basis), 35 parts of curing agent component; water accounts for 30% of the sum of phosphogypsum and curing agent by weight. The curing agent contains 4% silica fume, 9% limestone powder, 39% ultrafine granulated blast furnace slag powder, 8% metakaolin, 8% calcium aluminate powder, 32% silicate cement clinker powder, 0.5‰ suspension stabilizer, and 0.8‰ hydroxypropyl methylcellulose ether. Weigh each raw material, where the weighed phosphogypsum raw material is the mass of dry phosphogypsum converted by moisture content, and the weighed water should be discounted by the moisture contained in the wet phosphogypsum.

[0095] S3. Evenly mix the silica fume, limestone powder, ultrafine granulated blast furnace slag powder, metakaolin, calcium aluminate powder, silicate cement clinker powder, suspension stabilizer and hydroxypropyl methylcellulose ether required for the curing agent components in a dry mixing device to form a filling curing agent powder.

[0096] S4. Mix water and curing agent powder evenly in a stirring device to obtain curing agent slurry.

[0097] S5. Add the phosphogypsum into the curing agent slurry at a uniform speed until the slurry is evenly mixed to obtain the phosphogypsum filling slurry.

[0098] S6. Take part of the filling material slurry to test its expansion, take another part of the filling material slurry to test its water seepage rate, and put the remaining phosphogypsum filling material slurry into the setting time mold and the 70.7×70.7×70.7mm triple mold for setting time test and compressive strength test respectively. After curing to the specified age, test the compressive strength and pH value of the leachate.

[0099] The material detection method is the same as in Example 1 and will not be described again here.

[0100] Comparative Example 1: S1. Wet phosphogypsum should be dried at 40℃ to constant weight and its moisture content should be calculated.

[0101] S2, 70 parts of dihydrate phosphogypsum (on a dry basis), 30 parts of P·O 42.5 ordinary Portland cement component; water accounts for 34% of the sum of phosphogypsum and P·O 42.5 ordinary Portland cement by weight. Weigh each raw material, where the phosphogypsum raw material weighed is the mass of dry phosphogypsum converted by moisture content, and the water weighed should be deducted from the moisture contained in the wet phosphogypsum.

[0102] S3. Mix water and P·O 42.5 ordinary Portland cement powder evenly in a stirring device to obtain a slurry.

[0103] S4. Add the phosphogypsum into the slurry at a uniform speed until the slurry is evenly mixed to obtain the phosphogypsum filling slurry.

[0104] S5. Take part of the filling material slurry to test its expansion, take another part of the filling material slurry to test its water seepage rate, and put the remaining phosphogypsum filling material slurry into the setting time mold and the 70.7×70.7×70.7mm triple mold for setting time test and compressive strength test respectively. After curing to the specified age, test the compressive strength and pH value of the leachate.

[0105] The material detection method is the same as in Example 1 and will not be described again here.

[0106] Comparative Example 2 S1. Wet phosphogypsum should be dried at 40℃ to constant weight and its moisture content should be calculated.

[0107] S2, 70 parts of dihydrate phosphogypsum (on a dry basis), 30 parts of curing agent, wherein the curing agent comprises 60% granulated blast furnace slag powder, 30% P·O 42.5 ordinary Portland cement component, and 10% lime; water accounts for 34% of the sum of phosphogypsum and P·O 42.5 ordinary Portland cement by weight. Weigh each raw material, wherein the weighed phosphogypsum raw material is the mass of dry phosphogypsum converted by moisture content, and the weighed water should be deducted from the moisture contained in the wet phosphogypsum.

[0108] S3. Mix water and P·O 42.5 ordinary Portland cement powder evenly in a stirring device to obtain a slurry.

[0109] S4. Add the phosphogypsum into the slurry at a uniform speed until the slurry is evenly mixed to obtain the phosphogypsum filling slurry.

[0110] S5. Take part of the filling material slurry to test its expansion, take another part of the filling material slurry to test its water seepage rate, and put the remaining phosphogypsum filling material slurry into the setting time mold and the 70.7×70.7×70.7mm triple mold for setting time test and compressive strength test respectively. After curing to the specified age, test the compressive strength and pH value of the leachate.

[0111] The material detection method is the same as in Example 1 and will not be described again here.

[0112] Comparative Example 3 S1. Wet phosphogypsum should be dried at 40℃ to constant weight and its moisture content should be calculated.

[0113] S2, 65 parts of dihydrate phosphogypsum (on dry basis), 35 parts of curing agent component; water accounts for 34% of the sum of phosphogypsum and curing agent by weight. 5% silica fume, 10% limestone powder, 35% ultrafine granulated blast furnace slag powder, 20% metakaolin, 15% calcium aluminate powder, 15% silicate cement clinker powder, 0.5‰ suspension stabilizer, 0.8‰ hydroxypropyl methylcellulose ether.

[0114] Weigh each raw material, wherein the phosphogypsum raw material weighed is the mass of dry phosphogypsum converted by moisture content, and the water weighed should be deducted from the moisture contained in the wet phosphogypsum.

[0115] S3. Evenly mix the silica fume, limestone powder, ultrafine granulated blast furnace slag powder, metakaolin, calcium aluminate powder, silicate cement clinker powder, suspension stabilizer and hydroxypropyl methylcellulose ether required for the curing agent components in a dry mixing device to form a filling curing agent powder.

[0116] S4. Mix water and curing agent powder evenly in a stirring device to obtain curing agent slurry.

[0117] S5. Add the phosphogypsum into the curing agent slurry at a uniform speed until the slurry is evenly mixed to obtain the phosphogypsum filling slurry.

[0118] S6. Take part of the filling material slurry to test its expansion, take another part of the filling material slurry to test its water seepage rate, and put the remaining phosphogypsum filling material slurry into the setting time mold and the 70.7×70.7×70.7mm triple mold for setting time test and compressive strength test respectively. After curing to the specified age, test the compressive strength and pH value of the leachate.

[0119] The material detection method is the same as in Example 1 and will not be described again here.

[0120] Comparative Example 4 S1. Wet phosphogypsum should be dried at 40℃ to constant weight and its moisture content should be calculated.

[0121] S2, 80 parts of dihydrate phosphogypsum (on a dry basis), 20 parts of curing agent component; water accounts for 32% of the sum of phosphogypsum and curing agent by weight. Among them, the curing agent is composed of 5% silica fume, 10% limestone powder, 38% ultrafine granulated blast furnace slag powder, 10% metakaolin, 7% calcium aluminate powder, 30% silicate cement clinker powder, 1‰ suspension stabilizer, and 1‰ hydroxypropyl methylcellulose ether by mass. Weigh each raw material, where the weighed phosphogypsum raw material is the mass of dry phosphogypsum converted by moisture content, and the weighed water should be discounted by the moisture contained in the wet phosphogypsum.

[0122] Weigh each raw material, wherein the phosphogypsum raw material weighed is the mass of dry phosphogypsum converted by moisture content, and the water weighed should be deducted from the moisture contained in the wet phosphogypsum.

[0123] S3. Evenly mix the silica fume, limestone powder, ultrafine granulated blast furnace slag powder, metakaolin, calcium aluminate powder, silicate cement clinker powder, suspension stabilizer and hydroxypropyl methylcellulose ether required for the curing agent components in a dry mixing device to form a filling curing agent powder.

[0124] S4. Mix water and curing agent powder evenly in a stirring device to obtain curing agent slurry.

[0125] S5. Add the phosphogypsum into the curing agent slurry at a uniform speed until the slurry is evenly mixed to obtain the phosphogypsum filling slurry.

[0126] S6. Take part of the filling material slurry to test its expansion, take another part of the filling material slurry to test its water seepage rate, and put the remaining phosphogypsum filling material slurry into the setting time mold and the 70.7×70.7×70.7mm triple mold for setting time test and compressive strength test respectively. After curing to the specified age, test the compressive strength and pH value of the leachate.

[0127] The material detection method is the same as in Example 1 and will not be described again here.

[0128] Comparative Example 5 S1. Wet phosphogypsum should be dried at 40℃ to constant weight and its moisture content should be calculated.

[0129] S2, 70 parts of dihydrate phosphogypsum (on a dry basis), 30 parts of curing agent component; water accounts for 32% of the sum of phosphogypsum and curing agent by weight. Among them, the curing agent is composed of 5% silica fume, 28% limestone powder, 30% metakaolin, 7% calcium aluminate powder, 30% silicate cement clinker powder, 1‰ suspension stabilizer, and 1‰ hydroxypropyl methylcellulose ether by mass ratio. Weigh each raw material, where the weighed phosphogypsum raw material is the mass of dry phosphogypsum converted by moisture content, and the weighed water should be discounted by the moisture contained in the wet phosphogypsum.

[0130] Weigh each raw material, wherein the phosphogypsum raw material weighed is the mass of dry phosphogypsum converted by moisture content, and the water weighed should be deducted from the moisture contained in the wet phosphogypsum.

[0131] S3. Evenly mix the silica fume, limestone powder, ultrafine granulated blast furnace slag powder, metakaolin, calcium aluminate powder, silicate cement clinker powder, suspension stabilizer and hydroxypropyl methylcellulose ether required for the curing agent components in a dry mixing device to form a filling curing agent powder.

[0132] S4. Mix water and curing agent powder evenly in a stirring device to obtain curing agent slurry.

[0133] S5. Add the phosphogypsum into the curing agent slurry at a uniform speed until the slurry is evenly mixed to obtain the phosphogypsum filling slurry.

[0134] S6. Take part of the filling material slurry to test its expansion, take another part of the filling material slurry to test its water seepage rate, and put the remaining phosphogypsum filling material slurry into the setting time mold and the 70.7×70.7×70.7mm triple mold for setting time test and compressive strength test respectively. After curing to the specified age, test the compressive strength and pH value of the leachate.

[0135] The material detection method is the same as in Example 1 and will not be described again here.

[0136] Comparative Example 6 S1. Wet phosphogypsum should be dried at 40℃ to constant weight and its moisture content should be calculated.

[0137] S2, 70 parts of dihydrate phosphogypsum (on a dry basis), 30 parts of curing agent component; water accounts for 31% of the sum of phosphogypsum and curing agent by weight. The curing agent contains 5% silica fume, 19% limestone powder, 36% ultrafine granulated blast furnace slag powder, 8% calcium aluminate powder, 32% silicate cement clinker powder, 0.5‰ suspension stabilizer, and 0.8‰ hydroxypropyl methylcellulose ether. Weigh each raw material, where the weighed phosphogypsum raw material is the mass of dry phosphogypsum converted by moisture content, and the weighed water should be discounted by the moisture contained in the wet phosphogypsum.

[0138] S3. Evenly mix the silica fume, limestone powder, ultrafine granulated blast furnace slag powder, metakaolin, calcium aluminate powder, silicate cement clinker powder, suspension stabilizer and hydroxypropyl methylcellulose ether required for the curing agent components in a dry mixing device to form a filling curing agent powder.

[0139] S4. Mix water and curing agent powder evenly in a stirring device to obtain curing agent slurry.

[0140] S5. Add the phosphogypsum into the curing agent slurry at a uniform speed until the slurry is evenly mixed to obtain the phosphogypsum filling slurry.

[0141] S6. Take part of the filling material slurry to test its expansion, take another part of the filling material slurry to test its water seepage rate, and put the remaining phosphogypsum filling material slurry into the setting time mold and the 70.7×70.7×70.7mm triple mold for setting time test and compressive strength test respectively. After curing to the specified age, test the compressive strength and pH value of the leachate.

[0142] The material detection method is the same as in Example 1 and will not be described again here.

[0143] Comparative Example 7 S1. Wet phosphogypsum should be dried at 40℃ to constant weight and its moisture content should be calculated.

[0144] S2, 65 parts of dihydrate phosphogypsum (on a dry basis), 35 parts of curing agent component; water accounts for 31% of the sum of phosphogypsum and curing agent by weight. Among them, limestone powder is 10%, ultrafine granulated blast furnace slag powder is 41%, metakaolin is 9%, calcium aluminate powder is 8%, and silicate cement clinker powder is 32%. Weigh each raw material, among which the weighed phosphogypsum raw material is the mass of dry phosphogypsum converted by moisture content, and the weighed water should be discounted by the moisture contained in the wet phosphogypsum.

[0145] S3. Evenly mix the silica fume, limestone powder, ultrafine granulated blast furnace slag powder, metakaolin, calcium aluminate powder, silicate cement clinker powder, suspension stabilizer and hydroxypropyl methylcellulose ether required for the curing agent components in a dry mixing device to form a filling curing agent powder.

[0146] S4. Mix water and curing agent powder evenly in a stirring device to obtain curing agent slurry.

[0147] S5. Add the phosphogypsum into the curing agent slurry at a uniform speed until the slurry is evenly mixed to obtain the phosphogypsum filling slurry.

[0148] S6. Take part of the filling slurry for slurry test on its expansion, take another part of the filling slurry for slurry test on its water seepage rate, and put the remaining phosphogypsum filling slurry into the setting time mold and the 70.7×70.7×70.7mm triple mold for setting time test and compressive strength test respectively. After curing to the specified age, test the compressive strength and pH value of the leachate.

[0149] The material detection method is the same as in Example 1 and will not be described again here.

[0150] Figure 1 The material test results of the phosphogypsum filling and curing materials according to the examples of the present invention and the comparative examples are shown.

[0151] Combination Figure 1 As can be seen from Comparative Example 1, conventional silicate cement has the problems of long initial setting time (1460min), low early strength (no strength formed in 3d), and high strength. As can be seen from Comparative Example 2, the curing agent system composed of conventional mineral admixtures, lime, and cement still has the problems of low early strength and high alkalinity, and cracks appear in the specimens after 28d of the test, indicating that the system has volume stability problems.

[0152] It can be seen from Comparative Example 3 that when the proportion of silicate cement in the curing agent system is reduced by 20%, due to the acidity of phosphogypsum as a whole, the system cannot provide sufficient alkalinity to form hydration products of granulated blast furnace slag powder and metakaolin dissolved silicon and aluminum silicon ions. In addition, due to the high content of calcium aluminate cement in this system, the hydration reaction quickly covers the curing agent particles, affecting the final strength.

[0153] It can be seen from Comparative Example 4 that when the curing agent ratio is reduced to 20%, sufficient strength cannot be formed.

[0154] It can be seen from Comparative Example 5 that by adjusting the proportion of granulated blast furnace slag powder in the curing agent and increasing the limestone powder and metakaolin components, the mechanical properties of the system are reduced due to the lack of reaction between the granulated blast furnace slag powder and the hydration products of gypsum and cement. In addition, due to the high water requirement of metakaolin, the viscosity of the system is also increased, and the expansion is reduced to 740 mm.

[0155] It can be seen from Comparative Example 6 that when there is no metakaolin component in the curing agent system, it cannot react with the hydration products of silicate cement clinker powder, calcium hydroxide, calcium carbonate and calcium aluminate, and the mechanical properties of the system decrease.

[0156] It can be seen from Comparative Example 7 that when there is no silica fume, hydroxypropyl methylcellulose ether and suspension stabilizer components in the curing agent system, the water bleeding rate of the system increases significantly to 3% and the expansion degree of the slurry decreases.

[0157] The present invention aims at the defects of the prior art phosphogypsum filling materials, such as long initial setting time, low early strength, high pH value of filling materials and high water seepage rate. The technical scheme formed by the present invention can achieve the filling slurry with a large amount of phosphogypsum (phosphogypsum accounts for ≥65% of the dry material mass) with an initial setting time of ≤8h, 3d compressive strength ≥1MPa, 7d compressive strength ≥3MPa, 28d strength ≥5MPa, filling slurry expansion ≥800mm, slurry water seepage rate ≤0.5%, and 28d filling body leachate pH ≤10, where d in 3d, 7d and 28d refers to days.

[0158] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A low-alkalinity, early-strength phosphogypsum filling and curing material, characterized in that: The raw material formula of the low-alkalinity, early-strength phosphogypsum filling and curing material includes phosphogypsum, a curing agent and water, wherein the phosphogypsum is dihydrate phosphogypsum, the phosphogypsum accounts for 65-75 parts on a dry basis, the curing agent accounts for 25-35 parts, and the water accounts for 27%-34% of the sum of the phosphogypsum and the curing agent by weight, wherein the curing agent includes silica fume, limestone powder, ultrafine granulated blast furnace slag powder, metakaolin, aluminate cement, silicate cement clinker powder, suspension stabilizer and hydroxypropyl methylcellulose ether, and by mass percentage, the content of aluminate cement is 6-8%, the content of silicate cement clinker powder is 28-32%, the aluminate cement includes calcium aluminate powder, the calcium aluminate powder includes monocalcium aluminate and / or monocalcium dialuminate, and the calcium carbonate content of the limestone powder is ≥80%.

2. The low-alkalinity, early-strength phosphogypsum filling and curing material according to claim 1, characterized in that: The specific surface area of ​​the calcium aluminate powder is ≥400m 2 / kg, Al2O3≥50%.

3. The low-alkalinity, early-strength phosphogypsum filling and curing material according to claim 1, characterized in that: The curing agent is composed of the following components by mass percentage: Silica fume 4~6%, limestone powder 9~11%, ultrafine granulated blast furnace slag powder 36~41%, metakaolin 8~12%, calcium aluminate powder 6~8%, Portland cement clinker powder 28~32%, suspension stabilizer 0.3~3‰ and hydroxypropyl methylcellulose ether 0.5~1.5‰.

4. The low-alkalinity, early-strength phosphogypsum filling and curing material according to claim 1, characterized in that: The silica fume is semi-densified or fully-densified silica fume, with a silicon dioxide content of ≥95%, an activity index of ≥110%, and a water demand ratio of ≤125%; The fineness of the limestone powder is 1000 mesh or above; The specific surface area of ​​the ultrafine granulated blast furnace slag powder is ≥600m 2 / kg, 28d activity index ≥105%; The Al2O3 content of the metakaolin powder is ≥35%, and the specific surface area is ≥600m 2 / kg, 28d activity index ≥105%; The silicate cement clinker powder has a tricalcium silicate content of ≥55% and a specific surface area of ​​≥350m 2 / kg; The particle size of the phosphogypsum is ≤4.75 mm.

5. The low-alkalinity, early-strength phosphogypsum filling and curing material according to claim 1, characterized in that: The phosphogypsum accounts for ≥65% of the dry material mass, and the dry material includes phosphogypsum and a curing agent. The initial setting time of the phosphogypsum filling and curing material is ≤8h, the 3d compressive strength is ≥1MPa, the 7d compressive strength is ≥3MPa, the 28d strength is ≥5MPa, the filling slurry expansion is ≥800mm, the slurry water seepage rate is ≤0.5%, and the pH value of the 28d filling body leachate is ≤10.

6. A method for preparing a low-alkalinity, early-strength phosphogypsum filling and curing material, characterized in that: The preparation method comprises: Silica fume, limestone powder, ultrafine granulated blast furnace slag powder, metakaolin, aluminate cement, silicate cement clinker powder, suspension stabilizer, and hydroxypropyl methylcellulose ether are uniformly mixed to form a curing agent powder, wherein the aluminate cement includes calcium aluminate powder, and the calcium aluminate powder includes monocalcium aluminate and / or monocalcium dialuminate. The calcium carbonate content of the limestone powder is ≥80%, the content of aluminate cement is 6-8% by mass, and the content of silicate cement clinker powder is 28-32% by mass; Mixing water and the curing agent powder evenly to obtain a curing agent slurry; and Add phosphogypsum to the curing agent slurry and mix until the slurry is uniform to obtain phosphogypsum filling slurry; wherein the phosphogypsum is dihydrate phosphogypsum, the phosphogypsum accounts for 65-75 parts on a dry basis, the curing agent accounts for 25-35 parts, and water accounts for 27%-34% by weight of the sum of the phosphogypsum and the curing agent.

7. The method for preparing the low-alkalinity, early-strength phosphogypsum filling and curing material according to claim 6, characterized in that: The specific surface area of ​​the calcium aluminate powder is ≥400m 2 / kg, Al2O3≥50%.

8. The method for preparing the low-alkalinity, early-strength phosphogypsum filling and curing material according to claim 6, characterized in that: In the step of forming the curing agent powder, by mass percentage, silica fume 4-6%, limestone powder 9-11%, ultrafine granulated blast furnace slag powder 36-41%, metakaolin 8-12%, calcium aluminate powder 6-8%, silicate cement clinker powder 28-32%, suspension stabilizer 0.3-3‰, and hydroxypropyl methylcellulose ether 0.5-1.5‰.

9. The method for preparing the low-alkalinity, early-strength phosphogypsum filling and curing material according to claim 6, characterized in that: The silica fume is semi-densified or fully-densified silica fume, with a silicon dioxide content of ≥95%, an activity index of ≥110%, and a water demand ratio of ≤125%; The fineness of the limestone powder is 1000 mesh or above; The specific surface area of ​​the ultrafine granulated blast furnace slag powder is ≥600m 2 / kg, 28d activity index ≥105%; The Al2O3 content of the metakaolin powder is ≥35%, and the specific surface area is ≥600m 2 / kg, 28d activity index ≥105%; The silicate cement clinker powder has a tricalcium silicate content of ≥55% and a specific surface area of ​​≥350m 2 / kg; The particle size of the phosphogypsum is ≤4.75 mm.

10. The method for preparing the low-alkalinity, early-strength phosphogypsum filling and curing material according to claim 6, characterized in that: The phosphogypsum accounts for ≥65% of the dry material mass, and the dry material includes phosphogypsum and a curing agent. The initial setting time of the phosphogypsum filling and curing material is ≤8h, the 3d compressive strength is ≥1MPa, the 7d compressive strength is ≥3MPa, the 28d strength is ≥5MPa, the filling slurry expansion is ≥800mm, the slurry water seepage rate is ≤0.5%, and the pH value of the 28d filling body leachate is ≤10.

Citation Information

Patent Citations

  • Mixed material for filling mine roadway

    CN102910888A

  • Method for making cored building material block by using solidified soda residue soil

    CN103304213A

  • High-ductility repair dry powder mortar and preparation method thereof

    CN103332909A

  • Interface mortar with ardealite-based hydraulicity composite cementing material as cementing material

    CN108585714A

  • Curing agent with higher curing ability and use method thereof

    CN109336506A

Cited By

  • Phosphogypsum low-alkalinity composite phosphorus-fluorine curing agent and preparation method thereof

    CN121945517A

  • A low-alkalinity composite phosphorus-fluorine curing agent for phosphogypsum and its preparation method

    CN121945517B

  • Phosphogypsum-based fluidified soil

    CN122541173A

  • High-activity self-repairing impermeable phosphogypsum filling curing agent and preparation and application thereof

    CN122789685A